Incidence of Reproductive Disorders in Cattle and Buffalo under Field Conditions in Eastern Plain Zone of Uttar Pradesh - Ashoo; Verma, Hukum Chand; Singh, Rakesh Kumar; Kumar, Rajesh; Ramakant; Diwakar, Raj Pal (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
This study was conducted in the Barabanki district of Uttar Pradesh on reproductive disorders in cattle and buffaloes under field  conditions. The information was generated from 120 farmers, 20 farmers from each of six selected villages, who had at least one milking  dairy animal at the time of the investigation. The information was generated regarding reproductive disorders of indigenous cattle,  crossbred cattle, and buffalo due to improper feeding, breeding, and healthcare management practices and was analyzed to explore the  incidence rate of reproductive disorders faced by dairy farmers in three categories of animals. The overall incidence rate of reproductive  disorders among indigenous cattle, crossbred cattle, and buffalo in the area surveyed revealed maximum incidence in buffalo (76.05  %) and minimum in indigenous cattle (48.77 %), the crossbreds being intermediate (72.62 %). Late maturity was the major problem in  indigenous cattle and anoestrus in buffalo. The incidence of repeat breeding was the highest in crossbred cattle. Dystocia, prolapse  and stillbirth were more in buffaloes, while abortion, RFM, and uterine infections were more in crossbred cattle. Reproductive disorders  like dystocia, prolapse, abortion and stillbirth were mostly treated by veterinarians; however, remaining reproductive disorders like  anoestrus, repeat breeding, uterine infection etc. were treated by dairy farmers and quacks through their own experiences by using  different type of indigenous technical knowledge. There is a need to create awareness about scientific animal husbandry practices  among dairy farmers of the region studied.
Keywords: Buffalo; Crossbred cattle; Dairy farmer; Incidence; Indigenous cattle; Reproductive disorders